Virally mediated gene manipulation in the adult CNS - Edry, Efrat; Lamprecht, Raphael; Wagner, Shlomo; Rosenblum, Kobi (Frontiers in Molecular Neuroscience, 2011)
Understanding how the CNS functions poses one of the greatest challenges in modern life science and medicine. Studying the brain is especially challenging because of its complexity, the heterogeneity of its cellular composition, and the substantial changes it undergoes throughout its life-span. The complexity of adult-brain neural networks results also from the diversity of properties and functions of neuronal cells, governed, inter alia, by temporally and spatially differential expression of proteins in mammalian brain cell populations. Hence, research into the biology of CNS activity and its implications to human and animal behavior must use novel scientific tools. One source of such tools is the field of molecular genetics – recently utilized more and more frequently in neuroscience research. Transgenic approaches in general, and gene targeting in rodents have become fundamental tools for elucidating gene function in the CNS. Although spectacular progress has been achieved over recent decades by using these approaches, it is important to note that they face a number of restrictions. One of the main challenges is presented by the temporal and spatial regulation of introduced genetic manipulations. Viral vectors provide an alternative approach to temporally regulated, localized delivery of genetic modifications into neurons. In this review we describe available technologies for gene transfer into the adult mammalian CNS that use both viral and non-viral tools. We discuss viral vectors frequently used in neuroscience, with emphasis on lentiviral vector (LV) systems. We consider adverse effects of LVs, and the use of LVs for temporally and spatially controllable manipulations. Especially, we highlight the significance of viral vector-mediated genetic manipulations in studying learning and memory processes, and how they may be effectively used to separate out the various phases of learning: acquisition, consolidation, retrieval, and maintenance.